XXX: a woman's right to pornography - McElroy, Wendy (St. Martin's Press, 1995)
An unconventional argument for the preservation of pornography asserts that pornography can serve to benefit the feminist movement and promote sexual freedom for women, and explores the historical relationship between women and pornography.
Section: xi, 243 pages ; 22 cm
Keywords: corps; cours; droits des femmes*; pornographie; premier cycle; sex1911; sexualité; thématiques